Klasyfikacja spółek notowanych na GPW w Warszawie z wykorzystaniem funkcji powiązań (copula functions) - Papla, Daniel (Classification of the companies listed on the WSE using a copula functions, 2006)
This paper presents an attempt of classification of the companies listed on the WSE based on dependency between theirs returns. The relationship between dependency and distance is used here. This relationship is described in [Jajuga, Walesiak 2004], Dependency between two companies could be measured in the traditional way, using linear correlation coefficient between returns, or using chosen copula function. In this paper one of the Archimedean copula function was used. The parameter theta of those function can be treated as a dependency measure, analogous to the linear correlation coefficient. The paper consist of three parts. In first part the methodology used in empirical example is presented. Comparison between portfolios based on classification of companies from WSE using copula function and portfolios based on classification using the linear correlation coefficient. Empirical example is discussed in the third part.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 271-279